Structure, biological activity, and a biomimetic partial synthesis of the lirofolines, novel pentacylic indole alkaloids from Tabernaemontana - Kam, T.S.; Low, Y.Y.; Lim, K.H.; Choo, Y.M.; Pang, H.S.; Etoh, T.; Hayashi, M.; Komiyama, K. (Elsevier, 2010)
Two new pentacyclic indole alkaloids, lirofolines A and B, possessing a novel rearranged ibogan ring system, are obtained from two Malayan Tabernaemontana species ( Tabernaemontana corymbosa and Tabernaemontana divaricata) and the structures are established by analysis of the spectroscopic data. A biomimetic partial synthesis of lirofoline A from ibogaine via the Polonovski reaction is carried out. Lirofolines A and B showed significant activity in reversing multidrug resistance in vincristine-resistant KB cells (IC50 3.4 and 7.5 µg/ml, respectively).